2007
DOI: 10.1093/bja/aem146
|View full text |Cite
|
Sign up to set email alerts
|

Epidural naloxone reduces postoperative nausea and vomiting in patients receiving epidural sufentanil for postoperative analgesia

Abstract: Epidural naloxone was effective in reducing PONV induced by epidural sufentanil and additionally enhanced the analgesic effect. Therefore, concomitant infusion of a small dose of epidural naloxone should be considered to reduce PONV, especially in patients at greater risk for PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…In terms of postoperative pain and complications, there were no significant differences between the two groups. Previously, it was revealed that PONV control reduced the pain VAS (20,21). In this study, there were no significant differences in pain and satisfaction VAS scores.…”
Section: Discussioncontrasting
confidence: 39%
“…In terms of postoperative pain and complications, there were no significant differences between the two groups. Previously, it was revealed that PONV control reduced the pain VAS (20,21). In this study, there were no significant differences in pain and satisfaction VAS scores.…”
Section: Discussioncontrasting
confidence: 39%
“…Other data suggest that an ultra‐low dose of naloxone augmented the anti‐nociceptive effect of morphine by enhancing the reuptake of excitatory amino acids from the synaptic cleft . Human studies from 2001 and 2007 imply that applying low doses of naloxone intrathecally could reduce opioid side effects and enhance analgesia . Results in an earlier study suggested that naloxone in low doses could release endorphins, or probably relocate endorphins from receptor sites .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative epidural administration of naloxone and opioids was omitted from our meta‐analysis. Studies have demonstrated efficacy of epidural naloxone in PONV . However, pharmacokinetic dissimilarities between epidural and intravenous administration of naloxone and opioids excluded these trials from collective data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated efficacy of epidural naloxone in PONV. 35,36 However, pharmacokinetic dissimilarities between epidural and intravenous administration of naloxone and opioids excluded these trials from collective data analysis. Finally, whereas seven of the nine studies administered morphine for analgesia, 11,[16][17][18][19][20][21] two studies used tramadol or fentanyl in managing postsurgical pain.…”
Section: Discussionmentioning
confidence: 99%